1995
DOI: 10.1007/bf01437568
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon ionization of an inner shell electron of the Cl atom

Abstract: Abstract.We have calculated, using second order perturbation theory, the two photon ionization cross section of a K-shell electron of chlorine for E = 1.6 keV incident photons. Two classes of intermediate states must be considered, those in which a ls electron moves to an empty p-orbital, and those in which an electron from an occupied p-orbital moves into the continuum. The first class of intermediate states is followed by the ejection of a pelectron into the continuum. The second class of intermediate states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The CATS code [24], which is an adaptation of Cowan's atomic structure codes [25], was used to calculate wavefunctions, energy levels, oscillator strengths, and plane-wave Born collision strengths within the configuration-average approximation. Electronimpact ionization, photo-ionization and auto-ionization cross sections were calculated using the multi-purpose ionization GIPPER code [26,27]. The latter two processes were calculated explicitly with distorted-wave continuum functions while the electron-impact ionization calculations used scaled hydrogenic cross sections that were designed to reproduce distorted-wave calculations.…”
Section: Methodsmentioning
confidence: 99%
“…The CATS code [24], which is an adaptation of Cowan's atomic structure codes [25], was used to calculate wavefunctions, energy levels, oscillator strengths, and plane-wave Born collision strengths within the configuration-average approximation. Electronimpact ionization, photo-ionization and auto-ionization cross sections were calculated using the multi-purpose ionization GIPPER code [26,27]. The latter two processes were calculated explicitly with distorted-wave continuum functions while the electron-impact ionization calculations used scaled hydrogenic cross sections that were designed to reproduce distorted-wave calculations.…”
Section: Methodsmentioning
confidence: 99%
“…The CATS code [15], which is an adaptation of Cowan's atomic structure codes [16], was used to calculate wavefunctions, energy levels, oscillator strengths and planewave Born (PWB) collision strengths within the configurationaverage approximation. Electron-impact ionization, photoionization and auto-ionization cross sections were calculated using the multi-purpose ionization GIPPER code [17,18]. The latter two processes were calculated explicitly with distorted-wave continuum functions while the electronimpact ionization calculations used scaled hydrogenic cross sections that were designed to reproduce distorted-wave calculations.…”
Section: Theorymentioning
confidence: 99%
“…By comparison with distorted wave calculations, scaled hydrogenic cross sections (Clark et al 1991b) were found to be sufficently accurate for ionization out of other levels. Photo-ionization cross sections from all levels in each ion stage were calculated (Abdallah et al 1995) using the distorted continuum functions. Auto-ionization rates for the doubly excited states of neutral helium were also calculated for the inclusion of auto-ionization and dielectronic capture.…”
Section: Computational Modelmentioning
confidence: 99%